2019
DOI: 10.1111/1747-0080.12550
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake, food addiction and nutrition knowledge in young people with mental illness

Abstract: Aim: The aim of this study was to comprehensively assess dietary intake, nutrition knowledge and food addiction in young people with mental illness. Methods: This was a three-arm cross-sectional study of 16-25-year-olds attending community mental health services who met criteria for: (i) first-episode psychosis (FEP), (ii) ultra-high risk for psychosis (UHR) or (iii) depression/ anxiety. Participants self-completed three validated questionnaires: (i) Australian Eating Survey, (ii) General Nutrition Knowledge Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
(46 reference statements)
1
23
0
1
Order By: Relevance
“…Criterion validity of the liking-based diet quality indexes in the present paper and others [53,60,61] is supported through ability to distinguish diet quality between patients with diagnosed depression versus controls as well as associations with the CRFS. We found lower diet quality across all of the diet quality indexes among those with depression, which agrees with previous literature (e.g., [62][63][64]). The results of this study are similar to those quantifying diet through traditional methods, such as a 24-h recall or food frequency questionnaire [65,66].…”
Section: Discussionsupporting
confidence: 92%
“…Criterion validity of the liking-based diet quality indexes in the present paper and others [53,60,61] is supported through ability to distinguish diet quality between patients with diagnosed depression versus controls as well as associations with the CRFS. We found lower diet quality across all of the diet quality indexes among those with depression, which agrees with previous literature (e.g., [62][63][64]). The results of this study are similar to those quantifying diet through traditional methods, such as a 24-h recall or food frequency questionnaire [65,66].…”
Section: Discussionsupporting
confidence: 92%
“…The overavailability of highly rewarding foods might lead to addiction-like behaviors as happens with tobacco, alcohol, and psychoactive drugs (Ziauddeen and Fletcher, 2013;Chen et al, 2017). A growing body of research reports many similarities between conventional addiction disorders and consumption of highly palatable food typical of WD in both animals (Jacques et al, 2019) and humans (Pursey et al, 2015;Teasdale et al, 2020). Some populations self-diagnose themselves as food addicts because of the environment full of hyperpalatable products (Hardman et al, 2015;Ruddock et al, 2019).…”
Section: Obesity Overweight and Wdmentioning
confidence: 99%
“…Whilst both reviews add valuable insights, they only reviewed a limited scope of interventions. Given treatments for FA could be highly varied due to the strong link with other mental health conditions including disordered eating behaviours [ 5 , 9 , 11 , 26 ], substance use disorders [ 10 ] and increased weight status [ 4 ], there are a range of treatments that could be beneficial for those with addictive eating. The scope and classifications of interventions of interest for the current review, therefore, include those interventions that were not reported in previous reviews such as dietary interventions, lifestyle modifications, medication, and surgery.…”
Section: Introductionmentioning
confidence: 99%